Low Abundance of Methanotrophs in Sediments of Shallow Boreal Coastal Zones With High Water Methane Concentrations - Broman, Elias; Sun, Xiaole; Stranne, Christian; Salgado, Marco G.; Bonaglia, Stefano; Geibel, Marc; Jakobsson, Martin; Norkko, Alf; Humborg, Christoph; Nascimento, Francisco J. A. (Frontiers in Microbiology, 2020)
Coastal zones are transitional areas between land and sea where large amounts of organic and inorganic carbon compounds are recycled by microbes. Especially shallow zones near land have been shown to be the main source for oceanic methane (CH4) emissions. Water depth has been predicted as the best explanatory variable, which is related to CH4 ebullition, but exactly how sediment methanotrophs mediates these emissions along water depth is unknown. Here, we investigated the relative abundance and RNA transcripts attributed to methane oxidation proteins of aerobic methanotrophs in the sediment of shallow coastal zones with high CH4 concentrations within a depth gradient from 10–45 m. Field sampling consisted of collecting sediment (top 0-2 cm layer) from eight stations along this depth gradient in the coastal Baltic Sea. The relative abundance and RNA transcripts attributed to the CH4 oxidizing protein (pMMO; particulate methane monooxygenase) of the dominant methanotroph Methylococcales was significantly higher in deeper costal offshore areas (36–45 m water depth) compared to adjacent shallow zones (10–28 m). This was in accordance with the shallow zones having higher CH4 concentrations in the surface water, as well as more CH4 seeps from the sediment. Furthermore, our findings indicate that the low prevalence of Methylococcales and RNA transcripts attributed to pMMO was restrained to the euphotic zone (indicated by Photosynthetically active radiation (PAR) data, photosynthesis proteins, and 18S rRNA data of benthic diatoms). This was also indicated by a positive relationship between water depth and the relative abundance of Methylococcales and pMMO. How these processes are affected by light availability requires further studies. CH4 ebullition potentially bypasses aerobic methanotrophs in shallow coastal areas, reducing CH4 availability and limiting their growth. Such mechanism could help explain their reduced relative abundance and related RNA transcripts for pMMO. These findings can partly explain the difference in CH4 concentrations between shallow and deep coastal areas, (and the relationship between CH4 concentrations and water depth.